Associations of Body Mass Index with Sexual Risk-Taking and Injection Drug Use among US High School Students - Galuska, Deborah A.; Kann, Laura; Robin, Leah; Lowry, Richard (Journal of Obesity, 2014)
The purpose of this study was to determine if body mass index (BMI) is associated with behaviors that may increase risk for HIV and other sexually transmitted diseases (STDs) among US high school students. We analyzed nationally representative data from the 2005–2011 national Youth Risk Behavior Surveys (YRBS) to examine associations of BMI categories with sexual risk behaviors and injection drug use among sexually active high school students, using sex-stratified logistic regression models. Controlling for race/ethnicity and grade, among female and male students, both underweight (BMI < 5th percentile) and obesity (BMI ≥ 95th percentile) were associated with decreased odds of being currently sexually active (i.e., having had sexual intercourse during the past 3 months). However, among sexually active female students, obese females were more likely than normal weight females to have had 4 or more sex partners (odds ratio, OR = 1.59), not used a condom at last sexual intercourse (OR = 1.30), and injected illegal drugs (OR = 1.98). Among sexually active male students, overweight (85th percentile ≤ BMI < 95th percentile) was associated with not using a condom at last sexual intercourse (OR = 1.19) and obesity was associated with injection drug use (OR = 1.42). Among sexually active students, overweight and obesity may be indicators of increased risk for HIV and other STDs.